The mediating effect of depressive syndrome on the relationship between adverse childhood experiences and chronic kidney diseases among middle-aged and older adults - Xinyao Luo; Ke Wang; Junzhe Ran; Zhuyun Zhang; Yupei Li; Baihai Su (Frontiers in Public Health)
BackgroundChronic kidney disease (CKD) is projected to rank among the top five causes of mortality by 2050. In addition to established risk factors, adverse childhood experiences (ACEs) have recently emerged as significant contributors to health risks, including CKD and depressive syndrome (DS). However, the mechanisms linking ACEs, DS, and CKD remain unclear. This study aims to explore the role of ACEs in CKD development, with a focus on the mediating effects of DS.MethodsThis retrospective cohort study analyzed data from 10,247 participants in the China Health and Retirement Longitudinal Study (CHARLS). Logistic regression models were applied to assess the associations between ACEs, DS, and incident CKD, adjusting for demographic and lifestyle factors. Mediation analysis was conducted to evaluate the role of DS in the relationship between ACEs and CKD.ResultsLogistic regression analysis indicated that participants with a history of ACEs were at higher risk for both DS and CKD. Mediation analysis demonstrated that DS partially mediated the associations between CKD and seven specific ACEs: physical abuse, household substance abuse, household mental illness, domestic violence, unsafe neighborhood, peer bullying, and parental disability. Notably, DS fully mediated the relationship between CKD and unsafe neighborhood.ConclusionACEs significantly influence CKD risk in middle-aged and older adults, with DS serving as a key mediator. These findings underscore the importance of early mental health interventions and ACE-focused preventive strategies to reduce the burden of CKD.